A preliminary investigation of prevalence of extended spectrum beta lactamases among enterobacteriaceae isolated from poultry farms in Ibadan, Nigeria (2015)
Background: -Antibiotic resistance and extended spectrum beta–lactamase (ESBL) producing enterobacteriaceae are global health concerns and major problems for the treatment of different infections caused by enterobacteriaceae. Objective: -This study was carried out to determine the prevalence of phenotypically identified ESBL producers in enterobacteriaceae strains isolated from poultry farms in Ibadan. Material and Methods: Enterobacteriaceae were isolated from faecal samples of 45 chickens from 3 farms in Ibadan, Nigeria. The E. coli strains in the isolates were identified by biochemical methods. The susceptibility of all enterobacteriaceae strains to selected β lactam antibiotics were tested by disc diffusion method. ESBL production was tested by double disk synergy test and MIC determination (8–512 μg/ml) Results: - A total of 40 Enterobacteriaceae strains were isolated and 20 of the strains were identified as E. coli while 20 were tagged other Enterobacteriaceae strains. The E. coli strains were generally susceptible to tested antibiotics while other Enterobacteriaceae were relatively resistant. All the tested Enterobacteriacea were susceptible to cefepine. 15% of E.coli isolates were resistant to amoxicillin/clavulaniz and 38.9% of other Enterobacteriaceace isolates were resistant to cefoxitin. 5% of E. coli strains and 25% of other Enterobacteriaceae produced ESBL with concentration range of ˂8 μg/ml and >512μg/ml for antibiotics used singly and in combination with clavulanic acid respectively. Conclusions: - This study showed low occurrence of ESBL in E. coli strains but relatively high occurrence in other Enterobacteriaceae in poultries in Ibadan, Nigeria.. Therefore, there is need to control the use of antibiotics in poultry feeds and livestock production.